Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1109/tsipn.2021.3067305
|View full text |Cite
|
Sign up to set email alerts
|

On Trajectory Design for Intruder Detection in Wireless Mobile Sensor Networks

Abstract: We address the problem of detecting the invasion of an intruder into a region of interest (ROI) which is monitored by a distributed bandwidth-constrained wireless mobile sensor network (WMSN). We design periodic trajectories for the mobile sensor nodes (MSNs) such that high detection probabilities are obtained while maintaining the MSNs' energy consumption low. To reduce the transmission and processing burden on the MSNs, we propose an operation algorithm based on two modes, surveying mode and conf irmation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In addition, the authors have also analysed the influence of the number of sensors, intruder speed on the probability of detection, detection accuracy, and false alarm rate and found that the proposed algorithm outperforms the other fusion algorithms. Another work presented in [ 14 ] proposed optimal trajectories for mobile sensors employed for intrusion detection in a given RoI. The proposed trajectories for mobile sensors will maximise the coverage area and reduce energy consumption, which would increase the lifetime of the sensor network, thus providing improved intrusion detection performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors have also analysed the influence of the number of sensors, intruder speed on the probability of detection, detection accuracy, and false alarm rate and found that the proposed algorithm outperforms the other fusion algorithms. Another work presented in [ 14 ] proposed optimal trajectories for mobile sensors employed for intrusion detection in a given RoI. The proposed trajectories for mobile sensors will maximise the coverage area and reduce energy consumption, which would increase the lifetime of the sensor network, thus providing improved intrusion detection performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is pivotal to mention that the above-discussed works [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] contribute significantly in the research domain. However, their models are validated through Monte Carlo simulation, which requires very high computation cost and time.…”
Section: Introductionmentioning
confidence: 99%